2013
DOI: 10.1188/13.onf.394-402
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Predictors of Depression Among Older African American Patients With Cancer

Abstract: Purpose To determine whether psychosocial factors predict depression among older African American cancer patients. Design/Methods A descriptive correlational study. Setting Outpatient oncology clinic of NCI designated Cancer Center in Southeastern U.S. Sample African American cancer patients aged 50 and over. Methods Fisher’s Exact and Wilcoxon Rank Sum tests were used to evaluate differences between patients who were possibly depressed (Geriatric Depression Scale) or not. Multivariate linear regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
(64 reference statements)
1
20
0
Order By: Relevance
“…In particular, recently published studies have demonstrated that church-based emotional support has protective mental health benefits, including functioning as a stress buffer for African American adults who experience serious psychological distress (Nguyen et al 2017b) and lowering depressive symptoms (Hamilton et al 2013;Holt et al 2017). In a 2011 study by Chatters et al, African Americans' subjective closeness to their church members was negatively associated with suicidal ideation (Chatters et al 2011).…”
Section: Social Network Social Support and African American Mentalmentioning
confidence: 99%
“…In particular, recently published studies have demonstrated that church-based emotional support has protective mental health benefits, including functioning as a stress buffer for African American adults who experience serious psychological distress (Nguyen et al 2017b) and lowering depressive symptoms (Hamilton et al 2013;Holt et al 2017). In a 2011 study by Chatters et al, African Americans' subjective closeness to their church members was negatively associated with suicidal ideation (Chatters et al 2011).…”
Section: Social Network Social Support and African American Mentalmentioning
confidence: 99%
“…It can significantly compromise a quality of life and length of hospital stay, complications with therapy, ability to care for oneself and survival time in patients with cancer (12). Cancer patients who are depressed are less likely to participate in treatment decisions and to seek out social support, and more likely to have declines in physical functioning during treatment, to drop out of treatment and to Jpn J Clin Oncol 2014;44(4)311-317 doi:10.1093/jjco/hyu002 Advance Access Publication 5 February 2014 have shorter survival times than those who are not depressed (13). Many research studies have focused on the impact of depression on treatment outcomes, such as mortality or disease progression, among cancer patients (14).…”
Section: Introductionmentioning
confidence: 99%
“…Depression is associated with decreased cytotoxic and natural‐killer‐cell activities that can influence processes including immune surveillance of tumours and modulating somatic mutations and genomic instability . Depressed patients may be less compliant with treatment regimens and may be slower to present when there are relapses or acute symptoms …”
Section: Discussionmentioning
confidence: 99%